The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0956797616671327
|View full text |Cite
|
Sign up to set email alerts
|

A Window of Opportunity for Cognitive Training in Adolescence

Abstract: In the current study, we investigated windows for enhanced learning of cognitive skills during adolescence. Six hundred thirty-three participants (11–33 years old) were divided into four age groups, and each participant was randomly allocated to one of three training groups. Each training group completed up to 20 days of online training in numerosity discrimination (i.e., discriminating small from large numbers of objects), relational reasoning (i.e., detecting abstract relationships between groups of items), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 42 publications
(59 reference statements)
3
54
0
1
Order By: Relevance
“…Either reducing working memory load, decreasing time constraints, or training working memory and fluid ability capacity in such populations may therefore be promising lines of inquiry for intervention studies. It is worth highlighting, however, that cognitive training studies have so far shown little evidence of (far) transfer: Training abstract reasoning, a common measure of g f , has not resulted in robust increases in working memory (Knoll et al 2016) and working memory training has not been shown to transfer to reasoning skills or school performance (Dunning et al 2013; Schwaighofer et al 2015). Similarly, transfer from processing speed to reasoning seems to be limited (Mackey et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Either reducing working memory load, decreasing time constraints, or training working memory and fluid ability capacity in such populations may therefore be promising lines of inquiry for intervention studies. It is worth highlighting, however, that cognitive training studies have so far shown little evidence of (far) transfer: Training abstract reasoning, a common measure of g f , has not resulted in robust increases in working memory (Knoll et al 2016) and working memory training has not been shown to transfer to reasoning skills or school performance (Dunning et al 2013; Schwaighofer et al 2015). Similarly, transfer from processing speed to reasoning seems to be limited (Mackey et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, is followed by a significantly higher focus on and capability for divergence in late childhood and adolescence. 47,49,50 It is not entirely clear, however, whether this extends to all domains of life or is restricted to, for instance, social interactions. 15 What role does material culture play here?…”
Section: Cross-culturally Children Find Ways Of Incorporating Play Imentioning
confidence: 99%
“…Given the continuing development of language and communication in adolescence, the window of opportunity for improving cognitive function is much wider than once thought (Knoll et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…While interventions for language and communication difficulties have been found to have moderate to large effect sizes in primary school children, there is limited research into the effectiveness of interventions in secondary school students (Cirrin and Gillam 2008). Given the continuing development of language and communication in adolescence, the window of opportunity for improving cognitive function is much wider than once thought (Knoll et al 2016).…”
Section: Introductionmentioning
confidence: 99%